Negative electrode material, secondary battery, and electric device
By covering SiOx and metal oxide layers on the surface of the silicon negative electrode material, the problem of volume expansion effect of the silicon negative electrode material during charging and discharging is solved, and the cycle stability and conductivity of the secondary battery are significantly improved.
Patent Information
- Application Number
- CN202411499386.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-02-11
AI Technical Summary
The silicon negative electrode material produces a volume expansion effect during the charge and discharge process, resulting in electrode failure and rapid attenuation of capacity, limiting its industrialization process.
By covering the SiOx layer on the surface of the silicon powder and the metal oxide layer on the surface of the SiOx layer, the average particle size of the silicon powder, the Poisson's ratio of the SiOx layer and the thickness of the metal oxide layer are controlled to satisfy specific parameters range to improve the stability and conductivity of the negative electrode material.
It effectively alleviates the volume expansion effect of the negative electrode material, improves the cycle stability of the secondary battery, and improves the conductivity and structural stability of the negative electrode material.
Smart Images

Figure BDA0005102881480000091 
Figure BDA0005102881480000101 
Figure BDA0005102881480000111
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a negative electrode material, a secondary battery and an electrical device. Background Art
[0002] With the rapid development of science and technology, secondary batteries are increasingly used in electric vehicles, hybrid vehicles, renewable energy storage and other fields. Lithium-ion secondary batteries are the main energy storage devices in today's new energy field.
[0003] As one of the four major base materials of secondary batteries, the research on negative electrode materials plays a vital role in improving the performance of lithium batteries. Silicon negative electrode materials have become one of the hot topics of current research due to their high theoretical specific capacity. However, silicon materials will produce a volume expansion effect during charging and discharging, which will eventually lead to a series of problems such as electrode failure and rapid capacity decay, which greatly limits its industrialization process.
[0004] In view of this, this application is filed. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a negative electrode material, a secondary battery and an electrical device, which can effectively alleviate the volume expansion effect of the negative electrode material and improve the cycle stability of the secondary battery.
[0006] To achieve the above-mentioned object, in a first aspect of the present application, the present application provides a negative electrode material, comprising a core, a SiO2 layer disposed on the surface of the core, x layer and disposed on the SiO x The metal oxide layer on the surface of the layer;
[0007] The core includes silicon powder;
[0008] The negative electrode material satisfies: 1.75≤(10b+c-1) / (lna)≤3;
[0009] Wherein, a nm is the average particle size of the silicon powder;
[0010] b is SiO x Poisson's ratio of the layer;
[0011] c nm is the thickness of the metal oxide layer.
[0012] As an embodiment of the present application, the metal oxide includes at least one of aluminum oxide, copper oxide, magnesium oxide, manganese oxide, and nickel oxide.
[0013] As an implementation scheme of the present application, it satisfies: 200≤a≤1000.
[0014] As an implementation scheme of the present application, the following is satisfied: 0.15≤b≤0.45.
[0015] As an implementation scheme of the present application, it satisfies: 8≤c≤15.
[0016] As an implementation scheme of the present application, the Dv50 of the secondary particles of the negative electrode material is 3 to 10 μm, and the Dv50 of the secondary particles of the negative electrode material is the particle size corresponding to when the cumulative volume distribution percentage of the negative electrode material reaches 50%.
[0017] As an embodiment of the present application, the specific surface area of the negative electrode material is 1.6 to 5.6 m 2 / g; and / or
[0018] The compaction density of the negative electrode material is 1.5 to 2.3 g / cm 3 .
[0019] As an embodiment of the present application, the SiO x The total thickness of the layer and the metal oxide layer is 15 to 30 nm.
[0020] In a second aspect of the present application, the present application provides a secondary battery comprising the negative electrode material described above.
[0021] In a third aspect of the present application, the present application provides an electrical device, comprising the secondary battery described above.
[0022] The beneficial effects of the present invention are as follows: the present invention coats SiO on the surface of silicon powder x layer, and in SiO x The surface of the layer is coated with a metal oxide layer, and the average particle size of the silicon powder, SiO x The Poisson's ratio of the layer and the thickness of the metal oxide layer satisfy: 1.75≤(10b+c-1) / (lna)≤3. The coating thickness of the negative electrode material is appropriate, the coating integrity is good, good mechanical support is provided, the stability of the negative electrode material is effectively improved, the path length of lithium ion transmission can be improved, and the structure has better stability during lithium removal and lithium insertion, the conductivity of the negative electrode material is improved, the volume expansion effect of the negative electrode material is effectively alleviated, and the cycle stability of the secondary battery is improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a schematic diagram of the structure of the negative electrode material of the present application. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0025] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0026] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0027] like Figure 1 As shown, the embodiment of the present application provides a negative electrode material, including a core, and a SiO disposed on the surface of the core. x layer and disposed on the SiO x The metal oxide layer on the surface of the layer;
[0028] The core includes silicon powder;
[0029] The negative electrode material satisfies: 1.75≤(10b+c-1) / (lna)≤3;
[0030] Wherein, a nm is the average particle size of the silicon powder; b is SiO x The Poisson's ratio of the layer; c nm is the thickness of the metal oxide layer.
[0031] The present invention creatively coats SiO on the surface of silicon powder. x layer, and in SiO x The surface of the layer is coated with a metal oxide layer, and the average particle size of the silicon powder, SiO xThe Poisson's ratio of the layer and the thickness of the metal oxide layer satisfy: (10b+c-1) / (lna)<6. In this way, the coating thickness of the negative electrode material is appropriate, the coating integrity is good, and good mechanical support can be provided. In addition, the SiOx layer has the characteristics of plastic deformation, and the metal oxide of the outer layer has a high hardness. During the charge and discharge process, the plasticity of the middle SiOx layer can buffer the volume expansion effect, and the metal oxide of the outer layer provides a stable interface, thereby effectively improving the stability of the negative electrode material, and can improve the path length of lithium ion transmission. It has better structural stability during the process of lithium removal and lithium insertion, improves the conductivity of the negative electrode material, effectively alleviates the volume expansion effect of the negative electrode material, and improves the cycle stability of the secondary battery.
[0032] In one embodiment, in order to further optimize the cycle stability of the secondary battery, the negative electrode material satisfies: 1.9≤(10b+c-1) / (lna)≤2.4, for example, it can be 1.9, 2.1, 2.2, 2.3, 2.4 or a range consisting of any two of these values.
[0033] In one embodiment, the metal oxide includes at least one of aluminum oxide, copper oxide, magnesium oxide, manganese oxide, and nickel oxide. In particular, when such metal oxides are used, they can provide better mechanical support, provide a good interface, and improve the stability of the material.
[0034] In one embodiment, it satisfies: 200≤a≤1000, for example, it can be 200, 300, 400, 500, 600, 700, 800, 900, 1000 or a range consisting of any two of these values. The average particle size of the silicon powder is within this range, and can be well coated by the coating layer to avoid the generation of cracks, improve the coating integrity, effectively alleviate the volume expansion effect, and improve the cycle performance.
[0035] In one embodiment, the following is satisfied: 0.15≤b≤0.45, for example, it may be 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, 0.45 or a range consisting of any two of these values. x The Poisson's ratio of the SiO layer is within this range. x The layer has a certain plasticity and can form new contact points by deformation to adapt to the volume expansion effect of the negative electrode material during the charging and discharging process, avoid the decomposition and reconstruction of the SEI film, and effectively improve the interface stability of the negative electrode material.
[0036] It should be noted that Poisson's ratio refers to the ratio of the transverse normal strain to the axial normal strain when the material is subjected to unidirectional tension or compression, also known as the transverse deformation coefficient. It is an elastic constant that reflects the transverse deformation of the material. The SiO xThe test method of the Poisson's ratio of the layer is: the elastic parameters of the material are obtained by measuring the propagation speed of the elastic wave in the solid sample using the ultrasonic pulse echo method. When the elastic wave propagates in the isotropic elastic medium, according to the propagation theory of elastic waves in solids, the propagation speed of sound waves of different modes in the solid is related to the corresponding elastic modulus and density of the material. This method first measures the Young's modulus and shear modulus of the material according to the theoretical formula of the propagation of elastic waves in solids, and then calculates it through the formula υ=E / 2G-1. Among them, υ is the Poisson's ratio, E is the Young's modulus, and G is the shear modulus.
[0037] In one embodiment, the following is satisfied: 8≤c≤15, for example, it can be 8, 9, 10, 11, 12, 13, 14, 15 or a range consisting of any two of these values. By controlling the thickness of the metal oxide layer within the range of the present application, the coating thickness is appropriate, the coating integrity is good, and a suitable lithium ion diffusion path can be provided, thereby avoiding the lithium ion diffusion path being too long, and having better structural stability during the de-lithiation and lithium insertion processes.
[0038] In one embodiment, the Dv50 of the secondary particles of the negative electrode material is 3 to 10 μm, for example, it can be 3 μm, 5 μm, 8 μm, 10 μm or a range consisting of any two of these values. The Dv50 of the secondary particles of the negative electrode material is the particle size corresponding to when the cumulative volume distribution percentage of the secondary particles of the negative electrode material reaches 50%. Controlling the Dv50 of the secondary particles of the negative electrode material within this range can enable the negative electrode material to have a suitable specific surface area, reduce the ion transmission path, and improve the overall performance of the battery.
[0039] It should be noted that the test of Dv50 mentioned in this application refers to GB-T 19077-2016 and is tested using a particle size analysis laser diffractometer.
[0040] In one embodiment, the specific surface area of the negative electrode material is 1.6 to 5.6 m 2 / g, for example, it can be 1.6m 2 / g, 2m 2 / g, 4m 2 / g, 5m 2 / g, 5.6m 2 / g or a range consisting of any two of these values. Studies have found that the specific surface area of the negative electrode material will affect the contact sufficiency with the electrolyte when it is subsequently prepared into a secondary battery, and will also affect the ion transmission rate. When the specific surface area of the negative electrode material is within the above range, the secondary battery has a relatively excellent charge and discharge performance.
[0041] It should be noted that the specific surface area mentioned in this application is measured by the gas adsorption BET method in the reference standard "GB / T 19587-2017".
[0042] In one embodiment, the compaction density of the negative electrode material is 1.5 to 2.3 g / cm 3 , for example, it can be 1.5 g / cm 3 , 1.6g / cm 3 , 1.8g / cm 3 , 2g / cm 3 , 2.1g / cm 3 , 2.2g / cm 3 , 2.3g / cm 3 , or a range consisting of any two of the values. When the compaction density of the negative electrode material is within the above range, good contact between the negative electrode material particles can be ensured, which is beneficial to reducing resistance and improving the charge and discharge efficiency of the battery.
[0043] It should be noted that the compaction density mentioned in this application is obtained by calculating the sample mass / sample volume after rolling with a pressure of 40 kN.
[0044] In one embodiment, the SiO x The total thickness of the layer and the metal oxide layer is 15 to 30 nm, for example, it can be 15 nm, 16 nm, 18 nm, 20 nm, 22 nm, 24 nm, 25 nm, 26 nm, 28 nm, 30 nm or a range consisting of any two of these values. By controlling the total thickness within this range, the coating integrity is good, and at the same time, a suitable lithium ion diffusion path can be provided to avoid the lithium ion diffusion path being too long, and better structural stability is achieved during the de-lithiation and lithium insertion processes.
[0045] The thickness of the SiOx layer and the metal oxide layer mentioned in the present application is obtained by TEM transmission electron microscopy testing.
[0046] In one embodiment, the method for preparing the negative electrode material comprises the following steps:
[0047] The metal salt and the organic solvent are mixed evenly, and then silicon powder is added, stirred evenly, and dried to obtain a precursor. The precursor is ground and sieved, placed in a high-temperature tube furnace, and calcined by passing oxygen under an argon atmosphere to obtain a negative electrode material.
[0048] In one embodiment, the mass ratio of the metal salt to the organic solvent is 1:(4-20), for example, it can be 1:4, 1:5, 1:6, 1:8, 1:10, 1:12, 1:15, 1:18, 1:20 or a range consisting of any two of the values.
[0049] In one embodiment, the mass ratio of the metal salt to the silicon powder is 1:(10-30), for example, it can be 1:10, 1:12, 1:15, 1:18, 1:20, 1:22, 1:25, 1:28, 1:30 or a range consisting of any two of the values.
[0050] In one embodiment, the metal salt includes at least one of aluminum nitrate trihydrate, aluminum nitrate, aluminum sulfate, copper nitrate trihydrate, copper nitrate, copper sulfate, magnesium nitrate hexahydrate, magnesium nitrate, magnesium sulfate, manganese nitrate hexahydrate, manganese nitrate, manganese sulfate, nickel nitrate hexahydrate, nickel nitrate, and nickel sulfate.
[0051] In one embodiment, the organic solvent includes at least one of methanol, ethanol, propanol, N,N-dimethylformamide, acetonitrile, dimethyl sulfoxide, cyclopentane, tetrahydrofuran, 2-methyltetrahydrofuran, ethylene nitrate, ethylene carbonate, acetone, 1,4-butyrolactone and dimethylacetamide.
[0052] In one embodiment, the calcination temperature is 900-1200°C, for example, it can be 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C, 1200°C or a range consisting of any two of these values.
[0053] In one embodiment, the calcination time is 2 to 6 hours, for example, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours or a range consisting of any two values therein.
[0054] In one embodiment, the oxygen introduction rate is 150-200 mL / min.
[0055] In the second aspect of the present application, the present application provides a secondary battery, which includes a negative electrode plate, a positive electrode plate and a separator, the negative electrode plate includes a negative electrode collector and a negative electrode material layer arranged on at least one surface of the negative electrode collector, the negative electrode material layer includes a negative electrode material, and the negative electrode active material is the negative electrode material described above.
[0056] In the present application, there is no particular limitation on the negative electrode current collector, as long as the purpose of the present application can be achieved, for example, it can be copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper or a composite current collector.
[0057] In one embodiment, the negative electrode material layer further includes a conductive agent and a binder.
[0058] In one embodiment, the conductive agent includes at least one of carbon materials such as acetylene black, needle coke, carbon nanotubes, and graphene.
[0059] In one embodiment, the binder includes at least one of polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose, nitrocellulose, styrene-butadiene rubber, nitrile rubber, fluororubber, isoprene rubber, polybutadiene rubber, ethylene-propylene rubber, styrene-butadiene-styrene block copolymer or its hydrogenate, ethylene-propylene-diene terpolymer, styrene-ethylene-butadiene-ethylene copolymer, styrene-isoprene-styrene block copolymer, isotactic-1,2-polybutadiene, polyvinyl acetate, ethylene-vinyl acetate copolymer, propylene-α-olefin copolymer, polyvinylidene fluoride, polytetrafluoroethylene, fluorinated polyvinylidene fluoride, and polytetrafluoroethylene-ethylene copolymer.
[0060] In the secondary battery mentioned in the present application, a separator is usually provided between the positive electrode and the negative electrode to prevent short circuit. The separator includes a polyolefin film, an aromatic polyamide film, a polytetrafluoroethylene film, a polyethersulfone film, and the like.
[0061] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0062] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0063] In some embodiments, the type of the electrolyte is not specifically limited. The electrolyte includes an electrolyte salt and an organic solvent. The specific types of the electrolyte salt and the organic solvent are not specifically limited and can be selected according to actual needs. The electrolyte may also include additives. The types of the additives are not particularly limited and may be film-forming additives for the positive electrode and / or the negative electrode, or additives that can improve certain properties of the battery, such as additives that improve the high or low temperature performance of the battery.
[0064] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape.
[0065] An embodiment of the present application provides an electric device, comprising the secondary battery described above, wherein the secondary battery serves as a power supply for the electric device.
[0066] Exemplarily, the above-mentioned electrical devices may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0067] The present application is further described below with specific embodiments:
[0068] Example 1
[0069] A method for preparing a negative electrode material comprises the following steps:
[0070] 10 g of aluminum nitrate trihydrate and anhydrous ethanol were mixed evenly in a mass ratio of 1:10, and then 5 g of silicon powder with an average particle size of 400 nm was added, stirred evenly, and dried to obtain a precursor. The precursor was ground and sieved, and placed in a high-temperature tube furnace. Pure oxygen was introduced at a rate of 200 mL / min in a pure argon atmosphere, and the temperature was raised to 1000°C at 10°C / min. After calcining at 1000°C for 4 hours, it was naturally cooled to obtain a negative electrode material.
[0071] The negative electrode material prepared in this embodiment includes silicon powder, SiO 2 layer and disposed on the SiO 2 Aluminum oxide layer on the surface of the layer;
[0072] The parameters of the negative electrode material prepared in Example 1 are shown in Table 1.
[0073] Embodiments 2 to 7
[0074] The difference between Examples 2 to 7 and Example 1 is that in Examples 2 to 7, different oxygen atmospheres affect the SiO 2 The crystallinity, porosity and crystal structure of the layer can change the SiO 2 Poisson's ratio of the layer.
[0075] Embodiments 8 to 11
[0076] The difference between Examples 8 to 11 and Example 1 is that Examples 8 to 11 change the average particle size of silicon powder by changing the mesh size of the sieve.
[0077] Embodiments 12 to 14
[0078] The difference between Examples 12 to 14 and Example 1 is that Examples 12 to 14 change the thickness of the aluminum oxide layer by changing the mass of aluminum nitrate trihydrate and the calcination time.
[0079] Embodiment 15
[0080] The difference between Example 15 and Example 1 is that Example 15 uses copper nitrate trihydrate to replace aluminum nitrate trihydrate, thereby changing the type of metal oxide layer.
[0081] The negative electrode material prepared in this embodiment includes silicon powder, SiO 2 layer and disposed on the SiO 2 Copper oxide layer on the surface of the layer.
[0082] Example 16
[0083] The difference between Example 16 and Example 1 is that Example 16 uses magnesium nitrate hexahydrate to replace aluminum nitrate trihydrate, thereby changing the type of the metal oxide layer.
[0084] The negative electrode material prepared in this embodiment includes silicon powder, SiO 2 layer and disposed on the SiO 2 The magnesium oxide layer on the surface of the layer.
[0085] Embodiment 17
[0086] The difference between Example 17 and Example 1 is that Example 17 uses manganese nitrate hexahydrate to replace aluminum nitrate trihydrate, thereby changing the type of the metal oxide layer.
[0087] The negative electrode material prepared in this embodiment includes silicon powder, SiO 2 layer and disposed on the SiO 2 The manganese oxide layer on the surface of the layer.
[0088] Embodiment 18
[0089] The difference between Example 18 and Example 1 is that Example 18 uses nickel nitrate hexahydrate to replace aluminum nitrate trihydrate, thereby changing the type of metal oxide layer.
[0090] The negative electrode material prepared in this embodiment includes silicon powder, SiO 2 layer and disposed on the SiO 2 Nickel oxide layer on the surface of the layer.
[0091] Comparative Example 1
[0092] The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 changes the thickness of the aluminum oxide layer and the SiO 2 Poisson's ratio of the layer.
[0093] Comparative Example 2
[0094] The difference between Comparative Example 2 and Example 1 is that Comparative Example 2 changes the thickness of the aluminum oxide layer by changing the amount of aluminum nitrate trihydrate added and the calcination time.
[0095] Comparative Example 3
[0096] The difference between Comparative Example 3 and Example 1 is that Comparative Example 3 changes the oxygen introduction rate and thus changes the SiO 2 Poisson's ratio of the layer.
[0097] Comparative Example 4
[0098] The difference between Comparative Example 4 and Example 1 is that Comparative Example 4 changes the average particle size of silicon powder by changing the sieve mesh number.
[0099] Table 1
[0100]
[0101]
[0102] Test Case
[0103] The negative electrode materials prepared in each embodiment and comparative example are assembled into a secondary battery, and the preparation method is as follows:
[0104] (1) Preparation of negative electrode sheet
[0105] The negative electrode material: PVDF: conductive carbon black are homogenized in a ratio of 70:15:15, and the slurry is evenly coated on the negative electrode current collector, and then placed in an oven at 100°C for drying, and after drying, placed in a roller press under a pressure of 40 tons, and cut to obtain the negative electrode sheet;
[0106] (2) Preparation of positive electrode sheet
[0107] The positive electrode material lithium iron phosphate: PVDF: conductive carbon black is homogenized in a ratio of 85:7.5:7.5, and the slurry is evenly coated on the positive electrode current collector, and then placed in an oven at 100°C for drying, and after drying, placed in a roller press under a pressure of 40 tons, and cut to obtain a positive electrode sheet;
[0108] (3) Preparation of electrolyte
[0109] Equal volumes of ethylene carbonate (EC) and propylene carbonate (PC) are mixed uniformly to obtain an organic solvent, and then lithium hexafluorophosphate is uniformly dissolved in the organic solvent to obtain an electrolyte, wherein the concentration of lithium hexafluorophosphate is 1 mol / L.
[0110] (4) Preparation of secondary batteries
[0111] The present application has no specific restrictions on the preparation method. The positive electrode sheet, the negative electrode sheet and the PP separator can be made into an electrode assembly by lamination or winding. The outer packaging of the battery can be a hard shell or a soft package. There is no specific restriction on the shape of the battery.
[0112] 1. Cycle performance test:
[0113] Place the secondary battery in a charge and discharge test cabinet, keep the temperature at 25℃, charge rate 1C, discharge rate 1C, and perform cycle test. When the capacity drops to 80% of the initial capacity, stop the test and record the number of cycles.
[0114] 2. Negative electrode sheet resistance test:
[0115] Place the negative electrode sheet under a resistance meter to measure the resistance value of the negative electrode sheet.
[0116] 3. Rate performance test:
[0117] The secondary battery was placed in a charge and discharge test cabinet at a constant temperature of 25°C, and the charge rate was 1C, and the discharge rate was 1C and 5C, and the cycle was repeated 10 times. The discharge capacity after each cycle was recorded.
[0118] 4. Pole thickness change rate:
[0119] Take the negative electrode sheet of the secondary battery before and after the cycle in Test Example 1, place it under a SEM scanning electron microscope for observation, adjust the focus to obtain the thickness of the electrode sheet before and after the cycle, and calculate the thickness change rate.
[0120] 5. Volume expansion rate of negative electrode material:
[0121] Place the secondary battery in a charge and discharge test cabinet, keep the temperature at 25℃, charge at 1C, and charge the battery to 100% SOC. Disassemble the fully charged battery to obtain the fully charged negative electrode. Scrape off the coating layer on the electrode surface, place it under a laser particle size analyzer, and compare it with the negative electrode before the cycle to obtain the volume expansion rate of the negative electrode material.
[0122] Table 2
[0123]
[0124]
[0125] It can be seen from Table 2 that the negative electrode material of the present invention can effectively alleviate the volume expansion effect of the negative electrode material and improve the cycle stability of the secondary battery.
[0126] It can be seen from Tables 1 and 2 that the present invention can effectively alleviate the volume expansion effect of the negative electrode material and significantly improve the cycle stability of the secondary battery by satisfying the condition of 1.75≤(10b+c-1) / (lna)≤3 through the secondary battery.
[0127] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A negative electrode material, characterized in that: It comprises a core, a SiO2 layer arranged on the surface of the core, x layer and disposed on the SiO x The metal oxide layer on the surface of the layer; The core includes silicon powder; The negative electrode material satisfies: 1.75≤(10b+c-1) / (lna)≤3; Wherein, a nm is the average particle size of the silicon powder; b is SiO x Poisson's ratio of the layer; c nm is the thickness of the metal oxide layer.
2. The negative electrode material according to claim 1, characterized in that The metal oxide includes at least one of aluminum oxide, copper oxide, magnesium oxide, manganese oxide, and nickel oxide.
3. The negative electrode material according to claim 1, characterized in that Satisfies: 200≤a≤1000.
4. The negative electrode material according to claim 1, characterized in that Satisfies: 0.15≤b≤0.
45.
5. The negative electrode material according to claim 1, characterized in that Satisfies: 8≤c≤15.
6. The negative electrode material according to claim 1, characterized in that The Dv50 of the negative electrode material secondary particles is 3-10 μm, and the Dv50 of the negative electrode material secondary particles is the particle size corresponding to when the cumulative volume distribution percentage of the negative electrode material secondary particles reaches 50%.
7. The negative electrode material according to claim 1, characterized in that The specific surface area of the negative electrode material is 1.6 to 5.6 m 2 / g; and / or The compaction density of the negative electrode material is 1.5 to 2.3 g / cm 3 .
8. The negative electrode material according to claim 1, characterized in that The SiO x The total thickness of the layer and the metal oxide layer is 15 to 30 nm.
9. A secondary battery, characterized in that: The negative electrode material comprises any one of claims 1 to 8.
10. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to claim 9.